PENGASUHAN OTORITER BERPOTENSI MENURUNKAN KECERDASAN SOSIAL, SELF ESTEEM, DAN PRESTASI AKADEMIK REMAJA - Alfiasari, Alfiasari; Latifah, Melly; Wulandari, Astuti (Jurnal Ilmu Keluarga dan Konsumen, 2011)
Analysis of relation between parenting style perception and academic achievement, social intelligence, and self-esteem become the main issue of the research. This research involved 107 respondents of college students that consist of 55 male and 52 female of 1st grade. Respondents were chosen by proportional random sampling. Authoritative, authority, and permissive choosen as parenting style. Female students had significant correlation with authoritative perception scores. Meanwhile, family income had significant and positive correlation with permissive perception scores. Result showed that higher scores of authoritative that perceived by adolescents then higher scores of social intelligence and self-esteem. In the other hand, higher score of authoritarian that perceived by adolescents then lower scores of sosial intelligence, self-esteem, and academic achievement. Permissive parenting style had positive and significant correlation with academic achievement. Sosial intelligence had positive and significant correlation with self-esteem, meanwhile social intelligence and self-esteem did not had significant correlation with academic achievement.